The Winding Road to Power: Anwar Ibrahim in Malaysian Politics - Herdi Sahrasad; Ma'mun Murod Al-Barbasy; Al Chaidar; Muhammad Ridwan; Qusthan Firdaus (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
The relationship between Mahathir Mohamad and Anwar Ibrahim was colorful, from friendship, fellowship to violent conflict and hostilities, even Anwar was slandered with sodomy and jailed and tortured in his cell. Anwar's struggle in Malaysian politics was full of sorrow and bitterness, after being released from prison in 2007, in 2008 he was jailed again on charges of sodomy too. But then he could be free and form an opposition against Najib Razak who replaced Mahathir.In 1997, when he became a finance minister, Anwar Ibrahim supported the steps of the International Monetary Fund (IMF). He saved money by cutting state spending by 18 percent, cutting ministerial salaries, and postponing major projects. The major projects postponed by Anwar Ibrahim included a number of projects that were the mainstay of the development strategy designed by Mahathir Mohamad. In 1998, amid the worsening relationship between Anwar and Mahathir, Newsweek magazine named Anwar the "Asian Leader of the Year". In the same year, the youth wing of UMNO led by Anwar's ally Ahmad Zahid Hamidi indicated that they would raise the issue of cronyism and nepotism in the UMNO General Session.Now Anwar has returned to the Malaysian political scene and is waiting for the promise of Mahathir who will hand over the reign of the Prime Minister to him. Indeed, Anwar's way of life was full of mystery and grief but there was no grudge in him for those who had imprisoned him for quite a long time.